A Rare Cause of Postprandial Abdominal Pain - Lee, Jesse Zhen Cheng (J Surg Tech Case Rep, 2015)
A 49-year-old woman with medical history of polymyalgia rheumatica presented with 3 weeks history of epigastric pain worse after meal. Gallstones, peptic ulcer, bowel ischemia, bowel obstruction, gastroesophageal reflux disease, chest pathology, etc., were excluded from the study. Computerized tomography showed a short stenotic segment at coeliac trunk with poststenotic dilatation of 8 mm. Ultrasound scan showed peak velocity of 326 cm/s at the coeliac artery. Diagnosis of median arcuate ligament syndrome was made.